(untitled) (Research, Society and Development, 2024)
The hip joint in cats is a ball-and-socket joint formed by the head of the femur and the acetabulum of the pelvis, allowing a wide range of movements essential for the agility and flexibility of felines. However, a common orthopedic condition in cats is hip dysplasia, characterized by a malformation of the hip joint that results in instability and subsequent development of osteoarthritis. Thus, hip dysplasia can have a significant impact on the quality of life of cats, causing chronic pain, reduced mobility, and difficulty performing daily activities. Based on this, this work aims to describe the anatomy of the hip joint in cats, as well as present the anatomical changes and clinical implications of dysplasia for the health of these animals, through a literature review. This condition can be caused by genetic, nutritional, and environmental factors, so early identification and proper management are essential to minimize disease progression and improve the well-being of feline patients. Future studies are needed to better elucidate the etiology, improve diagnostic strategies, and develop more effective therapeutic options for hip dysplasia in cats.